Modeling Dynamical Positional Physical Data on Field Zones Occupied by Playing Positions in Elite-Level Futsal: A Comparison Between Running Velocities, Accelerations, and Decelerations. - Serrano, Carlos; Luis Felipe, Jose; García-Unanue, Jorge; Vicente Gimenez, Jesus; Jiménez-Linares, Luis; Ibáñez, Enrique; Hernando, Enrique; Gallardo, Leonor; Sánchez-Sánchez, Javier (Journal of Strength & Conditioning Research, 2023)
The aim of this study was to analyze the influence of playing positions on the physical demands and the specific court zones occupied during official futsal games. The total number of observations were 188, corresponding to 8 matches from the first division of the Spanish Futsal League during the 2019-2020 season. All dynamic motion representations were recorded using an 18 Hz device with ultra-wideband technology and local positioning system installed on the futsal pitch for each position. Python Data Analysis Library, Matplotlib, and Python programming language were applied as computational tools to generate visual analysis of figures to represent every physical demand analyzed. An analysis of variance test showed differences between playing positions, specifically, for winger position (p < 0.05). Based on eta-square coefficients, all variables showed large effects, except acceleration distance zone 1 (1-2 m·s-2). Accordingly, the visual representation of positional dynamic motion data showed differences in the physical demands and the court zone occupied by the different playing positions. This innovative visual analysis allows fitness coaches to associate the physical demands with court zones occupied by different playing positions, and it aids in the design of training drills associated with futsal competition requirements.